FTIR characterization of phytochemicals from Ipomoea aquatica Forsskal - SASIKALA .M; SUNDARAGANAPATHY .R; MOHAN .S (International Journal of Pharma and Bio Sciences, 2019)
FTIR is one of the best analyses to determine chemical structural properties of natural materials, as the vibrational frequencies of several modes of organic and inorganic molecules are active in the infrared. Hence this method is preferred for analyzing phytochemicals. The isolated compounds from hydro alcoholic extract of Ipomoea aquatica Forsskal whole plant were investigated using Fourier Transform Infra – Red (FTIR) spectroscopic analysis. The seven compounds with the sample code E01, E02, E05, W01, W02, W04 and W09 were subjected for characterization based on its purity and yield. The IR spectral data was analyzed between fingerprint region and functional group region of mid IR. From the interpretation of spectral data, the appeared bands for compounds come under classes of phytochemicals like E01 with alcohols/carboxylic acids/nitriles; E02 with alcohols/amines; E05 with alcohols/esters, W01 & W02 with carboxylic acids/nitro compounds; W04 with nitro compounds; W09 with alcohols/carboxylic acids/nitriles were detected along with the bands for alkyl halides in the W series. As per preliminary phytochemical evaluation of these compounds, they were reported as acidic for pH analysis and flavonoids (E01, E02 & E05) & tannins (W01, W02, W04 & W09) for phytochemical tests. The characterized functional groups will have an importance in semisynthetic applications and docking analysis to invent new drug molecules. The detected group of compounds from the isolates will definitely support the herbal medicines containing those to treat various ailments.